Adiponectin in Myopathies - Gamberi, Tania (Int J Mol Sci, 2019)
In skeletal muscle, adiponectin has varied and pleiotropic functions, ranging from metabolic, anti-inflammatory, insulin-sensitizing to regenerative roles. Despite the important functions exerted by adiponectin, the study of the hormone in myopathies is still marginal. Myopathies include inherited and non-inherited/acquired neuromuscular pathologies characterized by muscular degeneration and weakness. This review reports current knowledge about adiponectin in myopathies, regarding in particular the role of adiponectin in some hereditary myopathies (as Duchenne muscular dystrophy) and non-inherited/acquired myopathies (such as idiopathic inflammatory myopathies and fibromyalgia). These studies show that some myopathies are characterized by decreased concentration of plasma adiponectin and that hormone replenishment induces beneficial effects in the diseased muscles. Overall, these findings suggest that adiponectin could constitute a future new therapeutic approach for the improvement of the abnormalities caused by myopathies.